Markovian level set : a new method for boundary detection from echocardiographic images - Cheng, Jierong (2009)
Computer-based boundary detection in Echocardiographic Images is a challenging problem, due to the large amount of noise and the poor contrast presented. In this paper, a Markovian level set method is proposed for boundary detection in long-axis echocardiographic images. It combines MRF model which makes use of local statistics with level set method which handles topological changes, to ensure that the resulting boundary is continuous and smooth. Experimental results show that high accuracy is achieved with the proposed method.